Conserved vertebrate mir-451 provides a platform for Dicer-independent, Ago2-mediated microRNA biogenesis - Yang, Jr-Shiuan (National Academy of Sciences, 2010)
Canonical animal microRNAs (miRNAs) are generated by sequential cleavage of precursor substrates by the Drosha and Dicer RNase III enzymes. Several variant pathways exploit other RNA metabolic activities to generate functional miRNAs. However, all of these pathways culminate in Dicer cleavage, suggesting that this is a unifying feature of miRNA biogenesis. Here, we show that maturation of miR-451, a functional miRNA that is perfectly conserved among vertebrates, is independent of Dicer. Instead, structure-function and knockdown studies indicate that Drosha generates a short pre-mir-451 hairpin that is directly cleaved by Ago2 and followed by resection of its 3′ terminus. We provide stringent evidence for this model by showing that Dicer knockout cells can generate mature miR-451 but not other miRNAs, whereas Ago2 knockout cells reconstituted with wild-type Ago2, but not Slicer-deficient Ago2, can process miR-451. Finally, we show that the mir-451 backbone is amenable to reprogramming, permitting vector-driven expression of diverse functional miRNAs in the absence of Dicer. Beyond the demonstration of an alternative strategy to direct gene silencing, these observations open the way for transgenic rescue of Dicer conditional knockouts.